PENGARUH TUNJANGAN KINERJA, KEPEMIMPINAN, DAN PENGAWASAN INTERNAL TERHADAP KINERJA PEGAWAI PADA INSTITUT AGAMA ISLAM NEGERI SORONG - Sumarni Randriany; Herningsih Herningsih; Amiruddin Matutu (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
Basically, performance is the responsibility of each personnel who work in an organization or an institution. Good performance is reflected in optimal work results and according to organizational quality standards. Employee performance achievement can be influenced by various internal and external factors. The study was intended to analyze the performance of IAIN Sorong employees as measured by three determinant factors, namely performance allowances, leadership, and internal control. The population of this research is the employees of IAIN Sorong which consist of educators and educational staff who have received performance allowances with a sample size of 66 respondents. Data analysis used multiple linear regression, using the SPSS 19.0 application. The multiple regression equation obtained from the analysis is: Y = 0.468 X1 + 0.098 X2 + 0.580 X3. The results showed that partially the variable performance allowance, leadership, and internal control had a significant positive effect on employee performance variables. Simultaneously, these three factors affect the employee performance variable by 88.8%, while the remaining 11.2% is influenced by other factors outside of this research model.